PERANCANGAN USER INTERFACE (UI) & USER EXPERIENCE (UX) APLIKASI PENCARI KOST ABC DI KOTA XYZ MENGGUNAKAN METODE DESIGN THINKING - Mohammad Adam Prasetyo; Muhammad Choirul Rozikin; Renny Sari Dewi (Aisyah Journal Of Informatics and Electrical Engineering, 2021)
Boarding house can also be called a temporary lodging house. What is meant is the house that is used to stay for 1 day or more. The presence of boarding houses that exist today is of great benefit to the community, especially for people who are migrating. In this day and age where technology is growing rapidly, especially in information technology, which triggers many applications that are created with different uses. The ABC application is an application that can help find boarding. This application makes it easy for people who want to find boarding houses in the city of XYZ and its surroundings. This application is also equipped with information about the boarding house that will be searched for, for example: address, price, and other facilities in detail. In the design solution, User Interface (UI) & User Experience (UX) Design was chosen by using the Design Thinking method as a problem solution for boarding seekers so that it was easier to find detailed information about prices, addresses, and other facilities using only a smartphone. This User Interface (UI) & User Experience (UX) design serves to communicate the available system features so that users can understand and be able to use the system properly, and have satisfaction and comfort when using the application.